Insights into the high-temperature oxidation of methylcyclohexane. (1st April 2019) - Liu, Yalan; Li, Guangyue; Ding, Junxia
Abstract: Reactive molecular dynamics simulations were performed under different conditions in order to investigate in-detail the chemical events associated with high-temperature oxidation of methylcyclohexane (MCH). The corresponding kinetic behaviors of the major intermediates and products were systematically analyzed at the atomistic level. Thus the overall reaction scheme of MCH oxidation was established from the initial step to the final products. It was observed that the oxidation of MCH was mainly initiated by two kinds of reactions, including unimolecular decomposition and H abstraction, with the former being more important. In agreement with the available experimental results, C2 H4, CH2 O, CO, CO2 and H2 O were found to be the major products during the oxidation process. The results revealed that CH3 O2, CH3 O and C3 H5 O radicals were the precursors for CH2 O production, which was the key intermediate to generate CO. Additionally, C2 H3 O also had closed relationship with the formation of CO. For a better description of the combustion behavior, small oxides related to intermolecular reactions should be considered in the oxidation of MCH mechanisms. The temperature and density had a positive effect on the oxidation of MCH; it was also found that an increase of the equivalence ratio had a negligible effect on the MCH oxidation.